Acculturation and gestational weight gain in a predominantly puerto rican population - Tovar Alison; Chasan-Taber Lisa; Bermudez Odilia I; Hyatt Raymond R; Must Aviva (BMC, 2012)
Abstract Background Identifying risk factors that affect excess weight gain during pregnancy is critical, especially among women who are at a higher risk for obesity. The goal of this study was to determine if acculturation, a possible risk factor, was associated with gestational weight gain in a predominantly Puerto Rican population. Methods We utilized data from Proyecto Buena Salud, a prospective cohort study of Hispanic women in Western Massachusetts, United States. Height, weight and gestational age were abstracted from medical records among participants with full-term pregnancies (n=952). Gestational weight gain was calculated as the difference between delivery and prepregnancy weight. Acculturation (measured via a psychological acculturation scale, generation in the US, place of birth and spoken language preference) was assessed in early pregnancy. Results Adjusting for age, parity, perceived stress, gestational age, and prepregnancy weight, women who had at least one parent born in Puerto Rico/Dominican Republic (PR/DR) and both grandparents born in PR/DR had a significantly higher mean total gestational weight gain (0.9 kg for at least one parent born in PR/DR and 2.2kg for grandparents born in PR/DR) and rate of weight gain (0.03 kg/wk for at least one parent born in PR/DR and 0.06 kg/wk for grandparents born in PR/DR) vs. women who were of PR/DR born. Similarly, women born in the US had significantly higher mean total gestational weight gain (1.0 kg) and rate of weight gain (0.03 kg/wk) vs. women who were PR/ DR born. Spoken language preference and psychological acculturation were not significantly associated with total or rate of pregnancy weight gain. Conclusion We found that psychological acculturation was not associated with gestational weight gain while place of birth and higher generation in the US were significantly associated with higher gestational weight gain. We interpret these findings to suggest the potential importance of the US "obesogenic" environment in influencing unhealthy pregnancy weight gains over specific aspects of psychological acculturation.